Intelligent monitoring of solid state polymerization via molecular rotors: The case of poly(butylene succinate). (May 2016) - Jbilou, Fouzia; Georgousopoulou, Ioanna-Nektaria; Marinkovic, Sinisa; Vouyiouka, Stamatina; Papaspyrides, Constantine D.; Estrine, Boris; Dole, Patrice; Cottaz, Amandine; Joly, Catherine
Graphical abstract: Highlights: Solid state polymerization (SSP) was performed on poly(butylene succinate) (PBS). SSP is monitored for the first time by a fluorescent probe (CCVJ). Labelled PBS shows a decrease in the CCVJ fluorescence intensity and a blue shift during SSP process. CCVJ is able to act as a molecular rotor as well as a solvatochromic probe. Probe fluorescence lifetimes would show that 70% of CCVJ were localized in the amorphous regions of the PBS. Abstract: Solid state post-polymerization (post-SSP) was performed on poly(butylene succinate) (PBS) commercial- and synthesized-grades and monitored for the first time by means of a fluorescent probe: (9-2-carboxy-2-cyanovinyl)julolidine or CCVJ. CCVJ is a molecular rotor and was simply incorporated in the PBS bulk (100 ppm) for fluorescent labelling. Post-SSP runs were then performed following a one- or two-step process. During the one-step process, CCVJ labelled PBS presented a moderate molecular weight (MW) increase (up to 1.15 times) along with a post-crystallization effect. Next, the SSP effectiveness was improved (in terms of MW- up to 4.2 times- and thermal characteristic upgrade) with the addition of a precrystallization step (two-step process). Labelled PBS showed a decrease of the CCVJ fluorescence intensity and a respective significant wavelength shift (blue shift) with SSP time. According to CCVJ calibration, this behavior was ascribed to the resultant MW increment and to the decrease of the acidic index (AI) during SSP. CCVJ was proven a reliable sensor able to act as a molecular rotor as well as a solvatochromic probe sensing both the molecular weight and polarity changes in the course of PBS SSP process.